"Let me talk!" Silenced voices of International Graduate Students and A Need for Transcaring pedagogy - YILMAZ, TUBA (Journal of International Students, 2024)
International students in U.S. higher education programs often experienced discrimination due to their differences, exclusion or limited socialization with their mainstream peers, and lower academic success than their mainstream counterparts (Clements & Petray, 2021; Lin, 2012). This case study explored five international graduate students’ (three Chinese, one German, and one Arabic graduate student) experiences at a U.S. university. The data were collected through semi-structured interviews (Seidman, 2006) and analyzed with Domain analysis (Spradley,1979). The findings revealed that international graduate students associated native-like English practices with power. In addition, the participants often perceived discrimination due to their different languaging practices in the form of avoidance or disdain by their mainstream peers. Similarly, professors often affirmed the supremacy of mainstream culture and silenced them. These ‘uncaring practices’ contributed to international students’ oppression. These findings implied a need for transcaring pedagogy (García et al., 2012) in higher education programs.